Investigating the adoption of MOOCs : a technology-user-environment perspective - Ma, Long (2020)
In spite of the potentials promised by MOOCs (massive open online courses), the adoption rate of MOOCs is still low, especially in developing countries. Research on the adoption of MOOCs in developing countries is also limited. To fill this research gap, this research aims to study the adoption of MOOCs by extending current research on innovation and technology adoption in order to promote the diffusion of MOOCs in developing countries. Here, a conceptual framework, technology–user–environment was proposed to identify influential drivers and barriers of MOOC adoption. Eight hundred and twenty‐seven individuals in a developing country, were invited to participate in a questionnaire survey. Data were analysed by hierarchical regression, and the results show that for the (a) technological characteristics, perceived usefulness has the most significant influence, followed by lack of accessibility and performance‐to‐cost value; for the (b)user factors, self‐regulation was the most significant predictor of MOOC adoption, and female learners showed higher willingness to adopt MOOCs; and for the (c) social environmental factors, tradition and social norms and lack of information about MOOCs were negatively associated with adoption of MOOCs. Implications and suggestions are discussed at the end of this paper.